INDIGENOUS LANDS: : FROM THE COLONY TO CURRENTITY - Gabriela Carneiro; Silva de Souza, Bruna; Nascimento Pereira Batista, Eduardo; Menezes da Cruz Lima, Giovana (Revista Gênero e Interdisciplinaridade, 2021)
This article focuses on the problem of the demarcation of indigenous territory in Brazil, identifying the entire historical process, from colonization to the present day. Using a bibliographic search and presenting data and facts that justify all the obstacles that the indigenous people face since the arrival of the Portuguese, it was possible to identify all the problems surrounding indigenous territorial law. In addition, a descriptive research was carried out, based on a questionnaire to approximate what was presented with public opinion and to clarify the position of aborigines before society in general, today. Furthermore, the questions asked to the people, confirmed the thought that, over the years, the Indians have lost more than won, which is not only a matter of wealth, but of culture, history and legitimacy as the native people of that State. Therefore, it is clear that the evils of colonization still reflect in the lives of the indigenous people, who were formerly the “owners” of the land, today they must fight for their rights to guarantee their survival and the few demarcations that remain.